Strategies for the Formation of Monolayers From Diazonium Salts: Unconventional Grafting Media, Unconventional Building Blocks - Mattiuzzi, Alice; Lenne, Quentin; Carvalho Padilha, Janine; Troian-Gautier, Ludovic; Leroux, Yann R.; Jabin, Ivan; Lagrost, Corinne (Frontiers in Chemistry, 2020)
Pioneered by J. Pinson and coll. in 1990s, the reductive grafting of aryldiazonium salts has become a powerful method for surface functionalization. Highly robust interfaces result from this surface attachment, resistant to heat, chemical degradation and ultrasonication. Importantly, this approach can be applied to many materials, ranging from conducting, semi-conducting, oxides to insulating substrates. In addition, either massive, flat surfaces or nanomaterials can be functionalized. The method is easy to process and fast. The grafting process involves the formation of highly reactive aryl radicals able to attack the substrate. However, the generated radicals can also react with already-grafted aryl species, leading to the formation of loosely-packed polyaryl multilayer films, typically of 10-15 nm thick. It is thus highly challenging to control the vertical extension of the deposited layer and to form well-ordered monolayers from aryldiazonium salts. In this mini review, we briefly describe the different strategies that have been developed to prepare well-ordered monolayers. We especially focus on two strategies successfully used in our laboratories, namely the use of unconventional solvents, i.e. room temperature ionic liquids (RTILs), as grafting media and the use of calixarene macrocycles by taking benefit of their pre-organized structure. These strategies give large possibilities for the structuring of interfaces with the widest choice of materials and highlight the potential of aryldiazonium grafting as competitive alternative to SAMs of alkyl thiols.